The baby album - Fox, Roz Denny, 1939-; Copyright Paperback Collection (Library of Congress) (Toronto : New York : Harlequin, 2009)
"This isn't the life Casey Sinclair imagined. No husband, no job ... and a baby on the way. To pay the bills, Casey takes a position at Wyatt Keene's photography studio. It's not perfect, but what choice does she have? The fact that she finds Wyatt incredibly attractive is an unexpected bonus. But something's holding Wyatt back. And Casey thinks she knows what it is-- he's still grieving the loss of his wife and unborn child. So she hides her own pregnancy. As Casey and Wyatt get closer, it becomes more difficult for her to reveal her secret. Lying to her boss was a bad way to start, but how can Casey tell him the truth now-- just when everything she's always wanted is in reach?"--P. [4] of cover.
"Harlequin series spotlight"--Cover.
Keywords: Pregnant women -- Fiction; Widowers -- Fiction; Love stories